Can Sulfate Be the First Dominant Aqueous Sulfur Species Formed in the Oxidation of Pyrite by Acidithiobacillus ferrooxidans? - Borilova, Sarka; Mandl, Martin; Zeman, Josef; Kucera, Jiri; Pakostova, Eva; Janiczek, Oldrich; Tuovinen, Olli H. (Frontiers in Microbiology, 2018)
According to the literature, pyrite (FeS2) oxidation has been previously determined to involve thiosulfate as the first aqueous intermediate sulfur product, which is further oxidized to sulfate. In the present study, pyrite oxidation by Acidithiobacillus ferrooxidans was studied using electrochemical and metabolic approaches in an effort to extend existing knowledge on the oxidation mechanism. Due to the small surface area, the reaction rate of a compact pyrite electrode in the form of polycrystalline pyrite aggregate in A. ferrooxidans suspension was very slow at a spontaneously formed high redox potential. The slow rate made it possible to investigate the oxidation process in detail over a term of 100 days. Using electrochemical parameters from polarization curves and levels of released iron, the number of exchanged electrons per pyrite molecule was estimated. The values close to 14 and 2 electrons were determined for the oxidation with and without bacteria, respectively. These results indicated that sulfate was the dominant first aqueous sulfur species formed in the presence of bacteria and elemental sulfur was predominantly formed without bacteria. The stoichiometric calculations are consistent with high iron-oxidizing activities of bacteria that continually keep the released iron in the ferric form, resulting in a high redox potential. The sulfur entity of pyrite was oxidized to sulfate by Fe3+ without intermediate thiosulfate under these conditions. Cell attachment on the corroded pyrite electrode surface was documented although pyrite surface corrosion by Fe3+ was evident without bacterial participation. Attached cells may be important in initiating the oxidation of the pyrite surface to release iron from the mineral. During the active phase of oxidation of a pyrite concentrate sample, the ATP levels in attached and planktonic bacteria were consistent with previously established ATP content of iron-oxidizing cells. No significant upregulation of three essential genes involved in energy metabolism of sulfur compounds was observed in the planktonic cells, which represented the dominant biomass in the pyrite culture. The study demonstrated the formation of sulfate as the first dissolved sulfur-containing species with iron-oxidizing bacteria under high redox potential conditions. Minor aqueous sulfur intermediates may be formed but as a result of side reactions.